Variation of thermal properties of sandy loam soil under different management practices - MAITY, P; AGGARWAL, P (The Indian Journal of Agricultural Sciences, 2012)
To observe the effect of agronomical management practices on soil temperature (ST) and soil thermal properties, a field experiment was conducted during kharif season of 2008 at IARI, New Delhi on bare soil in split-plot design with three manure types as main treatment, ie green manure (GM) compost + charcoal and no manure, two land configuration (bed and flat system) as sub treatment and two mulch types transparent polyethylene (TP) and no polyethylene (NP) as sub-sub treatment. Diffusivity (D) values were higher for flat system than for bed system; in GM than in compost +charcoal and no manure treatments and also in TP than in NP. Thermal conductivity (K) was highest (12.51w/m/k) in flat system of green manure treatment under TP and lowest (0.75 w/m/k/) in bed system of no manure treatment under NP. Damping depth of green manure treatment with flat system under TP was extended up to 38.18 cm of soil depth but it was confined up to 9.52 cm only in bed of no manure treatment under NP. The temperatures were higher in compost + charcoal treatment as compared to no manure treatment because of black colour of the surface layer, which has more dominating effect on increase in the temperature because of more heat absorption even though the soil water content (SWC) was also higher in compost + charcoal treatment which resulted in higher CV and D but their effect in moderating the changes in ST were probably less significant.